Impaired conciousness and quality of life among post-traumatic brain injury patients at Hospital Universiti Sains Malaysia - Razak, Nur Ariedayu Abdul (Universiti Sains Malaysia, 2016)
Traumatic brain injury is defined as a disruption in the normal function of the brain that can be caused by a bump, blow, or jolt to the head or a penetrating head injury. Impaired consciousness is the first change in a client who traumatic brain injury. Clients that had TBI may experience impaired consciousness as well as affect their quality of life. The objective of this study is to assess the association between impaired consciousness and quality of life among post-traumatic brain injury patients at Hospital Universiti Sains Malaysia. A cross-sectional survey using a set of self-administered questionnaire from the Quality of Life after Brain Injury Tool. This study was conducted by follow-up telephone survey. A total of 55 respondents were involved in this study. Data was analyzed using SPSS version 22.0 and Chi-Square test was used to analyze descriptive data. A total of 56.4% (n=31) reported that majority of the participants were from 18-39 years old. Majority of respondents were male patients ,45(81.8%). Most of the respondents had high severity of TBI 16 (100%) had low quality of life and mild severity of TBI 16 (76.2%) had high quality of life. This study revealed that there was a significant association between the severity of TBI and quality of life (^>=0.000), while there were no significant association between location of TBI and quality of life (/?=0.532) , there were not significant association between selected demographic data age (p=0.443) and gender (p=0.286) with quality of life among post TBI patients at Hospital USM. In conclusion, post-traumatic brain injury patients with severe injury experienced low quality of life.